PERBANDINGAN PENGUKURAN MANUAL DAN SIMULASI MODEL TIME-VARYING UNTUK SUHU DAN ALIRAN UDARA - Maharani Maharani (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2009)
Considering the natural ventilation, the thermal behavior of buildings can be described by time-varying model. In this paper, we describe an implementation of model linear time-varying systems. We show the consequences of the model on computing time and accuracy. Finally, we compare experimental measures and simulation results using time-varying systems model. The model shows negligible difference in accuracy, and the computing time shortens.